Preparation and evaluation of tumour microenvironment response multistage nanoparticles for epirubicin delivery and deep tumour penetration. (5th November 2018) - Dai, Jialing; Han, Shangcong; Ju, Fang; Han, Mei; Xu, Lisa; Zhang, Ruoyu; Sun, Yong
Abstract: Poor tumour penetration became a major challenge for the use of nanoparticles in anticancer therapy. To further enhance the tumour penetration efficiency, we developed a tumour-microenvironment-responsive multistage drug delivery system which was formed layer by layer via electrostatic interaction with cationic drug-loaded nanoparticles, hyaluronidase (HAase) and iRGD-modified gelatin (G-iRGD). The drug-loaded nanoparticles were formed by self-assembling mPEG-PDPA-PG and encapsulation with epirubicin (EPI). Due to the protonation of tertiary amine groups of PDPA segment in acid environment, mPEG-PDPA-PG could enhance the lysosomal escape and the intracellular release of EPI. This NPs/HAase/G-iRGD delivery system showed great biocompatibility in vitro, confirmed by MTT method. In vitro spherical tumour model penetration and in vivo tumour permeability investigation showed HAase coated NPs-EPI (NPs-EPI/HAase) could significantly enhance its penetrating efficiency. The NPs-EPI/HAase could assist in breaking down the hyaluronic acid (HA), which was a key component of extracellular matrix and thereby improving mass transport within the solid tumours. The flow cytometry studies showed that G-iRGD coated NPs-EPI (NPs-EPI/G-iRGD) was more easily taken up by HepG2 cells than gelatin coated NPs-EPI (NPs-EPI/G), which revealed the active targeting ability of iRGD. The results proved that this NPs/HAase/G-iRGD delivery system showed promising potential in enhancing tumour penetration efficiency.